The Potential Role of Cell Penetrating Peptides in the Intracellular Delivery of Proteins for Therapy of Erythroid Related Disorders - Lefkothea C. Papadopoulou; Asterios S. Tsiftsoglou (MDPI AG, 2013)
The erythroid related disorders (ERDs) represent a large group of hematological diseases, which in most cases are attributed either to the deficiency or malfunction of biosynthetic enzymes or oxygen transport proteins. Current treatments for these disorders include histo-compatible erythrocyte transfusions or allogeneic hematopoietic stem cell (HSC) transplantation. Gene therapy delivered via suitable viral vectors or genetically modified HSCs have been under way. Protein Transduction Domain (PTD) technology has allowed the production and intracellular delivery of recombinant therapeutic proteins, bearing Cell Penetrating Peptides (CPPs), into a variety of mammalian cells. Remarkable progress in the field of protein transduction leads to the development of novel protein therapeutics (CPP-mediated PTs) for the treatment of monogenetic and/or metabolic disorders. The “concept” developed in this paper is the intracellular protein delivery made possible via the PTD technology as a novel therapeutic intervention for treatment of ERDs. This can be achieved via four stages including: (i) the production of genetically engineered human CPP-mediated PT of interest, since the corresponding native protein either is missing or is mutated in the erythroid progenitor cell (ErPCs) or mature erythrocytes of patients; (ii) isolation of target cells from the peripheral blood of the selected patients; (iii) ex vivo transduction of cells with the CPP-mediated PT of interest; and (iv) re-administration of the successfully transduced cells back into the same patients.